PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DI KELAS VIII.5 SMP NEGERI 3 PRABUMULIH - Amilia, Christien; Desmiati, Desmiati; Purwantari, Ema; Latina, Erna; Fadlia, Laila; Anggraini, Meri; Rahayu, Pamuji (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this action research was to know the increase in student learning outcomes after the implementation of the STAD type cooperative learning model, this study uses action research as many as three rounds. Each round consists of four stages, namely: design, activity and observation, reflexive, and refining. The method used in this study is the STAD type cooperative learning model. The target of this study is class VIII.5 Prabumulih 3 Public Middle School. The data obtained in the form of the final cycle test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that student learning outcomes increased from cycle I to cycle III, namely, cycle I (56.00%), cycle II (80.00%), cycle III (92.00%). The conclusion of this study is that the STAD type cooperative learning model can improve the learning outcomes of class VIII.5 of SMP Negeri 3 Prabumulih, and this learning model can be used as an alternative to learning civic education